1989
DOI: 10.1093/ajcp/91.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Anticoagulant Associated with Specific Inhibition of Factor VII in a Patient with AIDS

Abstract: A 37-year-old intravenous drug abuser with acquired immune deficiency syndrome showed elevated activated partial thromboplastin time (APTT) and prothrombin time, normal thrombin time and fibrinogen, and borderline low platelet counts. The patient subsequently had a fracture of the left zygomatic arch, which did not produce uncontrollable bleeding. The coagulogram repeated at this admission showed persistent elevation of APTT. Further coagulation workup showed the presence of a lupus anticoagulant with mild spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…penicillins (Mehta et al , 1992) and the cephalosporins (Kaiser et al , 1991) have been reported. Acquired factor VII inhibitors have also been reported occurring either spontaneously (Meade, 1988; Ndimbie et al , 1989; de Raucourt et al , 1994; Kamikubo et al , 2000) or in association with other diseases, e.g. myeloma (Elezovic et al , 1989).…”
Section: Acquired Factor VII Deficiencymentioning
confidence: 99%
“…penicillins (Mehta et al , 1992) and the cephalosporins (Kaiser et al , 1991) have been reported. Acquired factor VII inhibitors have also been reported occurring either spontaneously (Meade, 1988; Ndimbie et al , 1989; de Raucourt et al , 1994; Kamikubo et al , 2000) or in association with other diseases, e.g. myeloma (Elezovic et al , 1989).…”
Section: Acquired Factor VII Deficiencymentioning
confidence: 99%
“…The reasonably frequent finding of a lupus inhibitor in our patients further heightened the possibility that FVII deficiency may have been due to development of an associated auto-antibody to FVII. 5 The observation that new lupus inhibitors may develop after SCT has been previously reported from this institution. 24 However, having failed to demonstrate a neutralizing antibody to FVII by mixing experiments, we used ELISA to search for auto-antibodies to FVII(a).…”
Section: Discussionmentioning
confidence: 57%
“…Associated disease states have included malignancy, 2 aplastic anemia, 3,4 and antiphospholipid antibodies. 5,6 In stem cell transplant (SCT) patients, a modest reduction in FVII levels (in the 25 to 50% range) has been described in the first 2 weeks following SCT. [7][8][9] In these cases it has often been associated with deficiencies of other factors such as FXII or protein C. 10 It has been suggested that the fall in FVII and protein C levels in this setting may be a harbinger of veno-occlusive disease of the liver (VOD).…”
mentioning
confidence: 99%
“…Prothrombin antibodies are classically associated with lupus inhibitors [3][4][5][6] but antibodies to other clotting factors such as factors VII, VIII and X are described [7][8][9].…”
Section: Discussionmentioning
confidence: 99%